MANGROVE VEGETATION, TAMPARA VILLAGE, SOUTH KALEDUPA DISTRICT, WAKATOBI REGENCY, SOUTHEAST SULAWESI PROVINCE - Khairul Jamil; Katarina Hesty Rombe (Berkala Perikanan Terubuk, 2022)
Mangrove forest is a type of forest that grows in tidal areas, especially on protected beaches, lagoons, and river mouths whose vegetation communities can tolerate high salinity). This research began to be carried out from March to June located in Tampara village, South Kaledupa District, Wakatobi Regency, Southeast Sulawesi Province which aims to determine mangrove species, density, closure, and Important Value Index (IVI). The method used is line transect. The observations found 4 types of mangroves in the transect, namely Rhizophora stylosa, Bruguiera gymnorrhiza, Rhizophora mucronata, and Rhizophora apiculata. The density of trees and seedlings has a good density with an average of very dense criteria, while the mangrove sapling category has a damaged density and all stations have a rare density. The highest closure was Bruguiera gymnorrhiza 96.49% (station 4), the lowest was Rhizophora apiculata 2.75% (station 1). The highest overall IVI of mangroves was 200% of Rhizophora stylosa and Rhizophora mucronata (stations 2,3,4 and 7) and the lowest IVI was 39% of Rhizophora mucronata at station 5 seedling level.